PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN PENGUSAHA KENA PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA SIDOARJO UTARA - Mirdad Mirdad; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to analyze the effect of modernization of taxadministration system on taxpayers compliance level in Tax Service OfficePratama Sidoarjo North.The population of this study is Taxable Employersregistered in Tax Office Pratama Sidoarjo North. amounted to 223 people. Thismethod uses the method of Convenience sampling method with 46 respondents.This study uses primary data obtained through questionnaires. To test the relationof organizational structure, organizational procedure, organizational strategyand organizational culture to the level of taxable employer compliance, multiplelinear regression tests were used through SPSS software Ver 14. The result of theresearch shows that the variable of organizational structure has an effect on tothe level of compliance of taxable entrepreneur while the variable of procedure,organization, organizational strategy and organizational culture have no effect ontaxpayer compliance level.Keywords: Modernization of tax administration system, organizational structure,organization procedure, organizational strategy, and organizationalculture, taxable entrepreneur.